An electrochemical immunosensor based on prussian blue@zeolitic imidazolate framework-8 nanocomposites probe for the detection of deoxynivalenol in grain products. (30th March 2023) - Yuan, Zhenhong; Dai, Huang; Liu, Xiaodan; Duan, Shuo; Shen, Yafang; Zhang, Qi; Shu, Zaixi; Xiao, Anhong; Wang, Jiahua
Highlights: A novel electrochemical probe PB@ZIF-8/PDA/IgG was proposed. The advantages of PB, ZIF-8 and PDA collaborated to enhance detection sensitivity. The developed immunosensor had a detection limit of 0.0186 pg mL −1 . Proposed immunosensor was used for detection of deoxynivalenol in grain products. Abstract: The presence of deoxynivalenol (DON) in grains poses a threat to human health, which is critical for sensitive detection of DON. In this electrochemical immunosensor, zeolitic imidazolate framework-8 (ZIF-8) loaded with Prussian blue (PB) nanoparticles was coated by polydopamine (PDA) as a redox probe. The high porosity of ZIF-8, the unique electrochemical activity of PB and the outstanding electrical conductivity of PDA improved the sensitivity of the immunosensor. Under the optimized conditions, the peak current in differential pulse voltammetry displayed a good linear relationship over DON concentrations in a range of 0.1–5000 pg mL −1 with a detection limit of 0.0186 pg mL −1 . In addition, the immunosensor also had good selectivity and stability. Good recoveries of 85.67 to 118.00 % have been achieved for the detection of DON in spiked grain products. This new strategy exhibits great potential for simple and rapid detection of DON in grain and feed products.